High-hardness conductive polytetrafluoroethylene plastic as well as preparation method and application thereof

By adding hard carbon, glass carbon, long carbon fiber, nanocarbon and carbon nanotubes as fillers to the polytetrafluoroethylene conductive film, the existing polytetrafluoroethylene conductive film has been solved, and the comprehensive performance improvement of high hardness and conductivity has been achieved.

CN119591995APending Publication Date: 2025-03-11ZHUZHOU HONGDA POLYMER MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411861256.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing polytetrafluoroethylene conductive films have low hardness and are not resistant to wear, making it difficult to meet the application requirements of high hardness and conductivity.

Method used

Polytetrafluoroethylene is used as the matrix and hard carbon, glass carbon, long carbon fiber, nanocarbon and carbon nanotubes are added as fillers. Through formula innovation and preparation process optimization, the hardness and conductivity of the material are improved.

Benefits of technology

It significantly improves the hardness of the material to more than 80 Shore hardness, enhances processing performance and wear resistance, and broadens the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591995A_ABST
    Figure CN119591995A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polytetrafluoroethylene materials, in particular to high-hardness conductive polytetrafluoroethylene plastic and a preparation method thereof.The high-hardness conductive polytetrafluoroethylene plastic takes polytetrafluoroethylene as a matrix and takes hard carbon, glassy carbon, long carbon fibers, nanocarbon and carbon nanotubes as filler; the hard carbon and the glassy carbon are mixed to jointly improve the hardness, the long carbon fibers serve as a framework to improve the bending strength, the nanocarbon improves the compatibility among the fillers, and the carbon nanotubes mainly improve the conductivity of the material and reduce the resistance value of the material. According to the high-hardness conductive polytetrafluoroethylene plastic disclosed by the invention, the formula is innovated, the polytetrafluoroethylene is used as a matrix, and five fillers are added and mixed, so that the hardness of the material can be improved, the strength and the conductivity are also considered, and the overall performance of the whole material is excellent. The product prepared by the preparation method of the high-hardness conductive polytetrafluoroethylene plastic is high in stability, the density of the product meets the use requirement, and risks such as cracks are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-hardness conductive polytetrafluoroethylene plastic and a preparation method and application thereof, belonging to the technical field of polytetrafluoroethylene materials. Background Art

[0002] Polytetrafluoroethylene is a thermoplastic polymer that is a white solid at room temperature with a density of about 2200 kg / m 3 . PTFE, like all fluorocarbons, derives its properties from the polymerization of carbon-fluorine bonds. The only chemicals known to affect these carbon-fluorine bonds are highly reactive metals such as alkali metals, and at higher temperatures metals such as aluminum and magnesium, and fluorides such as xenon difluoride and cobalt fluoride. PTFE is a fluorocarbon solid, a polymeric compound composed entirely of carbon and fluorine, that has a wide range of uses.

[0003] Pure PTFE skived film has low hardness, soft texture, poor creep resistance, easy deformation, poor thermal conductivity, large linear thermal expansion coefficient, and is easy to expand and crack, affecting normal use. Using inorganic fillers to fill modified PTFE can significantly improve the shortcomings of PTFE such as poor thermal conductivity, poor creep resistance, and poor wear resistance, greatly expanding the application range of PTFE.

[0004] CN201810537763.8 discloses a polytetrafluoroethylene conductive film and a preparation method thereof. In terms of mass percentage, the conductive film is composed of 90-95% polytetrafluoroethylene, 3-6% modified carbon black and 2-4% graphite, and the modified carbon black is obtained by surface treatment of carbon black with N-(benzocyclobutene-4-yl) maleimide. N-(benzocyclobutene-4-yl) maleimide can improve the lipophilicity and dispersibility of carbon black, so that carbon black can be evenly dispersed in the polytetrafluoroethylene base material without agglomeration, and the polytetrafluoroethylene conductive film has excellent elongation at break and conductivity; the decomposition temperature of the modified carbon black reaches above 450°C, so that it still has excellent thermal stability at the polytetrafluoroethylene processing temperature of 370-390°C, and thermal decomposition will not occur; the composite synergistic effect of graphite and modified carbon black can further improve the thermal stability and conductivity of the polytetrafluoroethylene conductive film. However, the hardness cannot be improved, and the disadvantage of wear resistance has not been solved.

[0005] The invention of a high-hardness conductive polytetrafluoroethylene plastic with good hardness and wear resistance has great significance and market value in practical use and production. Summary of the invention

[0006] In order to solve the deficiencies of the above-mentioned prior art, the present invention provides a high-hardness conductive polytetrafluoroethylene plastic, which is prepared by using polytetrafluoroethylene as a matrix and hard carbon, glassy carbon, long carbon fiber, nanocarbon, and carbon nanotubes as fillers. The hardness of the product can be increased to above 80 Shore hardness, thereby increasing the processing performance and wear resistance of the material and broadening the scope of use of the high-hardness conductive polytetrafluoroethylene plastic.

[0007] The technical means adopted by the present invention to solve the above problems are: Disclosed is a high-hardness conductive polytetrafluoroethylene plastic, which uses polytetrafluoroethylene as a matrix and uses hard carbon, glassy carbon, long carbon fiber, nano carbon and carbon nano tubes as fillers; the hard carbon and glassy carbon are mixed to improve the hardness, the long carbon fiber serves as a skeleton to improve the bending strength, the nano carbon improves the compatibility between the fillers, and the carbon nano tube mainly improves the conductivity of the material and reduces the resistance value of the material.

[0008] This high-hardness conductive polytetrafluoroethylene plastic is innovative in formula, using polytetrafluoroethylene as the matrix and adding five fillers to the mixture. It not only improves the hardness of the material but also takes into account the strength and conductivity. The overall performance of the whole material is excellent.

[0009] Furthermore, the raw material formula includes the following components in parts by weight: 67 parts to 70 parts of polytetrafluoroethylene, 8 parts to 12 parts of hard carbon, 8 parts to 12 parts of long carbon fibers, 1 part to 3 parts of carbon nanotubes, 3 parts to 6 parts of glassy carbon, and 3 parts to 6 parts of nanocarbon.

[0010] Furthermore, the raw material formula includes the following components in parts by weight: 68 parts of polytetrafluoroethylene, 10 parts of hard carbon, 10 parts of long carbon fibers, 2 parts of carbon nanotubes, 5 parts of glassy carbon, and 5 parts of nanocarbon.

[0011] Furthermore, the average particle size of polytetrafluoroethylene is 25um; the particle size of hard carbon is 3-15um; the diameter of long carbon fiber is 5-7um, and the length is 240-250um; the particle size of carbon nanotube is 8-15nm in outer diameter, 3-5nm in inner diameter, and 3-15um in length; the particle size of glassy carbon is 200-400 mesh, and the particle size of nanocarbon is 5-10nm.

[0012] Another object of the present invention is to disclose a method for preparing the above-mentioned high-hardness conductive polytetrafluoroethylene plastic, which is characterized by comprising the following steps: S1. Prepare and mix the materials: weigh the ingredients of each component, mix the polytetrafluoroethylene with the long carbon fiber, then add the carbon nanotubes, nanocarbon, hard carbon, and finally add the glassy carbon, and mix them evenly; S2 pressing: The raw materials mixed in step S1 are pressed and molded by segmented pressing at a pressure of 18t-90t, a total pressing time of 8min-12min, and cold pressing at room temperature for 15-25min; S3. Sintering: The pressed green body is sintered, and the sintering process is as follows: heating from room temperature to 310℃-330℃ after 3h-5h, maintaining for 0.8h-2h; heating to 340-360℃ after 0.8h-1.5h, maintaining for 2h-4h, cooling to 310℃-330℃ after 0.8h-1.5h, and cooling to below 150℃ after 2-4h.

[0013] Furthermore, the mixing in step S1 is to first fully mix the polytetrafluoroethylene and the long carbon fiber at a rotation speed of 30000-40000 r / min, and mix for 1min-3min; then add the carbon nanotubes at a rotation speed of 18000r / min-22000r / min, mix for 0.8min-1.5min, then add the nanocarbon at a rotation speed of 18000-22000r / min, mix for 0.8min-1.5min, then add the hard carbon at a rotation speed of 23000-26000r / min, mix for 0.8min-1.5min, and finally add the glassy carbon at a rotation speed of 23000-26000r / min, mix for 1.5min-3.0min; 35000r / min-45000r / min, and mix for 1min-3min.

[0014] Furthermore, in step S2, the segmented pressing is divided into three stages, the first stage uses a pressure of 18t-20t for 45s-75s, the second stage uses a pressure of 50t-55t for 150s-240s, and the third stage uses a pressure of 85t-95t for 320s-390s.

[0015] The high-hardness conductive polytetrafluoroethylene plastic disclosed by the invention is applied to wafer cleaning and photoresist stripping operations, thermal insulators and bearings, wear-resistant rings, throat bushings and constant-axis bearings of fluid pumps.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The high-hardness conductive polytetrafluoroethylene plastic of the present invention is prepared by using polytetrafluoroethylene as a matrix and hard carbon, glassy carbon, long carbon fiber, nanocarbon, and carbon nanotubes as fillers. The hardness of the product can be increased to above 80 Shore hardness, thereby increasing the processing performance and wear resistance of the material and broadening the application scope of the high-hardness conductive polytetrafluoroethylene plastic.

[0017] 2. The high-hardness conductive polytetrafluoroethylene plastic of the present invention is innovative in formula, using polytetrafluoroethylene as a matrix and adding five fillers for mixing, which not only improves the hardness of the material but also takes into account the strength and conductivity, and the overall performance of the whole material is excellent.

[0018] 3. The product prepared by the method for preparing high-hardness conductive polytetrafluoroethylene plastic of the present invention has strong stability, the density of the product meets the use requirements, and there is no risk of cracks. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings constituting a part of the present application are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute an improper limitation of the present invention.

[0020] Figure 1 This is the sintering curve of the high-hardness conductive polytetrafluoroethylene plastic described in Example 1. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto. Example 1

[0022] The high-hardness conductive polytetrafluoroethylene plastic of this embodiment uses polytetrafluoroethylene as a matrix and uses hard carbon, glassy carbon, long carbon fibers, nanocarbon, and carbon nanotubes as fillers. The hard carbon and glassy carbon are mixed to improve the hardness together, the long carbon fibers serve as a skeleton to improve the bending strength, the nanocarbon improves the compatibility between the fillers, and the carbon nanotubes mainly improve the conductivity of the material and reduce the resistance value of the material.

[0023] The raw material formula includes the following components in parts by weight as shown in Table 1. Among them, the average particle size of polytetrafluoroethylene is 25um, the particle size of hard carbon is 3-8um, the diameter of long carbon fiber is 5-7um, and the length is 240-250um, the particle size of carbon nanotube is 8-10nm in outer diameter, 3-5nm in inner diameter, and 3-8um in length, the particle size of glassy carbon is 300 mesh, and the particle size of nano carbon is 5-8nm.

[0024] The specific preparation method comprises the following steps: S1. Prepare and mix the materials: weigh each component first, mix polytetrafluoroethylene with long carbon fiber first, then add carbon nanotubes, nanocarbon, hard carbon in sequence, and finally add glassy carbon, and mix evenly; the order of adding the raw materials cannot be messed up, otherwise it will affect the dispersion uniformity and the compatibility of each component, and the required hardness cannot be achieved. The mixing in this embodiment is to first fully mix polytetrafluoroethylene with long carbon fiber, with a speed of 35000r / min and mix for 2min; then add carbon nanotubes, with a speed of 20000r / min, mix for 1min, then add nanocarbon, 20000r / min, mix for 1min, then add hard carbon, with a speed of 25000r / min, mix for 1min, and finally add glassy carbon, 25000r / min, mix for 2min; 40000r / min, mix for 2min.

[0025] S2. Pressing: Press the raw materials mixed in step S1 into shape by segmented pressing at a pressure of 18t-90t for a total pressing time of 8min-12min and cold pressing at room temperature for 15-25min. Specifically, the pressing is divided into three stages in this embodiment. The first stage uses a pressure of 18t for 60s, the second stage uses a pressure of 54t for 180s, and the third stage uses a pressure of 90t for 360s. If cracks will appear on the over-pressed product, the pressure must reach the molding pressure during pressing, otherwise the density cannot be reached.

[0026] S3. Sintering: The pressed green body is sintered, and the sintering process is: from room temperature to 325℃ for 4 hours, maintained for 1 hour, then heated to 355℃ after 1 hour, maintained for 3 hours, then cooled to 325℃ after 1 hour, and cooled to 150℃ after 3 hours. Figure 1 shown.

[0027] The performance test results of the prepared high-hardness conductive polytetrafluoroethylene plastic are shown in Table 2. Example 2

[0028] The high-hardness conductive polytetrafluoroethylene plastic of this embodiment has the following raw material formula in weight percentage, as shown in Table 1. Among them, the average particle size of the polytetrafluoroethylene is 25um, the particle size of the hard carbon is 12-15um, the diameter of the long carbon fiber is 5-7um, and the length is 240-250um, the particle size of the carbon nanotube is 10-15nm in outer diameter, 3-5nm in inner diameter, and 12-15um in length, the particle size of the glassy carbon is 400 mesh, and the particle size of the nanocarbon is 9-10nm.

[0029] The specific preparation method comprises the following steps: S1. Prepare and mix the materials: weigh each component first, mix polytetrafluoroethylene with long carbon fiber first, then add carbon nanotubes, nanocarbon, hard carbon in sequence, and finally add glassy carbon, and mix evenly; the order of adding the raw materials cannot be messed up, otherwise it will affect the dispersion uniformity and the compatibility of each component, and the required hardness cannot be achieved. The mixing in this embodiment is to first fully mix polytetrafluoroethylene with long carbon fiber, with a speed of 30000r / min and mix for 3min; then add carbon nanotubes, with a speed of 22000r / min, mix for 0.8min, then add nanocarbon, 18000r / min, mix for 1.5min, then add hard carbon, with a speed of 26000r / min, mix for 0.8min, and finally add glassy carbon, 23000r / min, mix for 3min; then use 35000r / min as a whole and mix for 3min.

[0030] S2. Pressing: Press the raw materials mixed in step S1 into shape by segmented pressing at a pressure of 18t-90t for a total pressing time of 8min-12min and cold pressing at room temperature for 15-25min. Specifically, the pressing is divided into three stages in this embodiment. The first stage uses a pressure of 20t for 120s, the second stage uses a pressure of 50t for 180s, and the third stage uses a pressure of 80t for 420s. If cracks will appear on the over-pressed product, the pressure must reach the molding pressure during pressing, otherwise the density cannot be reached.

[0031] S3. Sintering: The pressed green body is sintered, and the sintering process is as follows: heating from room temperature to 330°C over 5 hours, maintaining for 0.8 hours, heating to 340°C after 0.8 hours, maintaining for 2 hours, cooling to 310°C after 0.8 hours, and cooling to 150°C after 4 hours.

[0032] The performance test results of the prepared high-hardness conductive polytetrafluoroethylene plastic are shown in Table 2. Example 3

[0033] The high-hardness conductive polytetrafluoroethylene plastic of this embodiment has the following raw material formula in weight percentage, as shown in Table 1. Among them, the average particle size of polytetrafluoroethylene is 25um, the particle size of hard carbon is 8-10um, the diameter of long carbon fiber is 5-7um, and the length is 240-250um, the particle size of carbon nanotube is 8-11nm in outer diameter, 3-5nm in inner diameter, and 8-10um in length, the particle size of glassy carbon is 300 mesh, and the particle size of nano carbon is 7-9nm.

[0034] The specific preparation method comprises the following steps: S1. Prepare and mix the materials: weigh each component first, mix polytetrafluoroethylene with long carbon fiber first, then add carbon nanotubes, nanocarbon, hard carbon in sequence, and finally add glassy carbon, and mix evenly; the order of adding the raw materials cannot be messed up, otherwise it will affect the dispersion uniformity and the compatibility of each component, and the required hardness cannot be achieved. The mixing in this embodiment is to first fully mix polytetrafluoroethylene with long carbon fiber, with a rotation speed of 40000r / min and mix for 1min; then add carbon nanotubes, with a rotation speed of 18000r / min, mix for 1.5min, then add nanocarbon, 22000r / min, mix for 0.8min, then add hard carbon, with a rotation speed of 23000r / min, mix for 1.5min, and finally add glassy carbon, 26000r / min, mix for 1min; then use 45000r / min as a whole and mix for 1min.

[0035] S2. Pressing: Press the raw materials mixed in step S1 into shape by segmented pressing at a pressure of 18t-90t for a total pressing time of 8min-12min and cold pressing at room temperature for 15-25min. Specifically, the pressing is divided into three stages in this embodiment. The first stage uses a pressure of 25t for 60s, the second stage uses a pressure of 55t for 90s, and the third stage uses a pressure of 80t for 330s. If cracks will appear on the over-pressed product, the pressure must reach the molding pressure during pressing, otherwise the density cannot be reached.

[0036] S3. Sintering: The pressed green body is sintered, and the sintering process is as follows: heating from room temperature to 310°C for 3 hours, maintaining for 2 hours, heating to 360°C after 1.5 hours, maintaining for 4 hours, cooling to 330°C after 1.5 hours, and cooling to 150°C after 2 hours. The performance test results of the prepared high-hardness conductive polytetrafluoroethylene plastic are shown in Table 2. Comparative Example 1-Comparative Example 5

[0037] Comparative Examples 1 to 5 are formulated according to the ingredients in Table 1, and the preparation method steps are the same as those of Example 1. The performance test results of the materials prepared using the comparative example methods are shown in Table 2.

[0038] The high-hardness conductive polytetrafluoroethylene plastic prepared by the method of this embodiment has a hardness significantly higher than that of the comparative example, and also has both strength and conductivity. The overall performance of the whole material is excellent.

[0039] The high-hardness conductive polytetrafluoroethylene plastic provided by the present invention exhibits excellent performance under corrosive wet chemical / plasma conditions and high temperatures. In wafer cleaning and photoresist stripping operation applications, it effectively improves the preventive maintenance cycle, exhibits good ultraviolet (UV) resistance in flat panel display applications, and is used as a thermal insulator and bearing in dry plasma applications. In refineries, chemical plants, power plants and other fluid pumps, it improves the reliability and performance of the pump, helps reduce the risk of pump jamming, and allows the internal rotating to stationary parts gap to be reduced by more than 50%.

[0040] Those skilled in the art may make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, all equivalent technical solutions should also fall within the protection scope of the present invention, and the protection scope of the present invention should be defined by the claims.

Claims

1. A high-hardness conductive polytetrafluoroethylene plastic, characterized in that: Polytetrafluoroethylene is used as a matrix, and hard carbon, glassy carbon, long carbon fiber, nanocarbon and carbon nanotubes are used as fillers; the hard carbon and glassy carbon are mixed to improve the hardness together, the long carbon fiber serves as a skeleton to improve the bending strength, the nanocarbon improves the compatibility between the fillers, and the carbon nanotubes mainly improve the conductivity of the material and reduce the resistance value of the material.

2. The high-hardness conductive polytetrafluoroethylene plastic according to claim 1, characterized in that: The raw material formula includes the following components in parts by weight: 67 parts to 70 parts of polytetrafluoroethylene, 8 parts to 12 parts of hard carbon, 8 parts to 12 parts of long carbon fibers, 1 part to 3 parts of carbon nanotubes, 3 parts to 6 parts of glassy carbon, and 3 parts to 6 parts of nano carbon.

3. The high-hardness conductive polytetrafluoroethylene plastic according to claim 2, characterized in that: The raw material formula includes the following components in parts by weight: 68 parts of polytetrafluoroethylene, 10 parts of hard carbon, 10 parts of long carbon fibers, 2 parts of carbon nanotubes, 5 parts of glassy carbon, and 5 parts of nano carbon.

4. The high-hardness conductive polytetrafluoroethylene plastic according to claim 3, characterized in that: The average particle size of polytetrafluoroethylene is 25um; the particle size of hard carbon is 3-15um; the diameter of long carbon fiber is 5-7um, and the length is 240-250um; the particle size of carbon nanotube is 8-15nm in outer diameter, 3-5nm in inner diameter, and 3-15um in length; the particle size of glassy carbon is 200-400 mesh, and the particle size of nanocarbon is 5-10nm.

5. A method for preparing the high-hardness conductive polytetrafluoroethylene plastic according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Prepare and mix the materials: weigh the ingredients of each component, mix the polytetrafluoroethylene with the long carbon fiber, then add the carbon nanotubes, nanocarbon, hard carbon, and finally add the glassy carbon, and mix them evenly; S2 pressing: The raw materials mixed in step S1 are pressed and molded by segmented pressing, with a pressure of 18t-90t, a total pressing time of 8min-12min, and cold pressing at room temperature for 15-25min; S3. Sintering: The pressed green body is sintered, and the sintering process is: heating from room temperature to 310°C-330°C for 3h-5h and maintaining for 0.8h-2h; After 0.8h-1.5h, the temperature is raised to 340-360℃, maintained for 2h-4h, and then lowered to 310℃-330℃ after 0.8h-1.5h, and then lowered to below 150℃ after 2-4h.

6. The method for preparing high-hardness conductive polytetrafluoroethylene plastic according to claim 5, characterized in that: The mixing in step S1 is to first fully mix the polytetrafluoroethylene and the long carbon fiber at a rotation speed of 30000-40000r / min for 1min-3min; then add the carbon nanotubes at a rotation speed of 18000r / min-22000r / min, mix for 0.8min-1.5min, then add the nanocarbon at a rotation speed of 18000-22000r / min, mix for 0.8min-1.5min, then add the hard carbon at a rotation speed of 23000-26000r / min, mix for 0.8min-1.5min, and finally add the glassy carbon at a rotation speed of 23000-26000r / min, mix for 1.5min-3.0min; then the whole is mixed at a rotation speed of 35000r / min-45000r / min for 1min-3min.

7. The method for preparing high-hardness conductive polytetrafluoroethylene plastic according to claim 5, characterized in that: In step S2, the segmented pressing is divided into three stages. The first stage uses a pressure of 18t-20t for 45s-75s, the second stage uses a pressure of 50t-55t for 150s-240s, and the third stage uses a pressure of 85t-95t for 320s-390s.

8. An application of the high-hardness conductive polytetrafluoroethylene plastic according to claims 1-7, characterized in that: Used in wafer cleaning and photoresist stripping operations, thermal insulators and bearings, fluid pump wear rings, throat bushings.

Citation Information

Patent Citations

  • Polytetrafluoroethylene (PTFE) conductive film and preparation method thereof

    CN108822452A